2019
DOI: 10.1111/cns.13092
|View full text |Cite
|
Sign up to set email alerts
|

Macrolide derivatives reduce proinflammatory macrophage activation and macrophage‐mediated neurotoxicity

Abstract: Summary Introduction Azithromycin (AZM) and other macrolide antibiotics are applied as immunomodulatory treatments for CNS disorders. The immunomodulatory and antibiotic properties of AZM are purportedly independent. Aims To improve the efficacy and reduce antibiotic resistance risk of AZM‐based therapies, we evaluated the immunomodulatory and neuroprotective properties of novel AZM derivatives. We semisynthetically prepared derivatives by altering sugar mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…AZM administration significantly reduced the mean rostral-caudal lesion length when given 30 min after injury ( p = 0.03; Figures 5A,B); the 3-h delivery timepoint was not statistically significant ( p = 0.55; Figure 5). Given that pro-inflammatory macrophages are neurotoxic and that AZM limits this activation in vitro we sought to quantify whether post-SCI AZM treatment improved the number of surviving neurons at 28 dpi (Zhang et al, 2015, 2019). However, AZM treatment did not affect neuron sparing throughout the rostral-caudal extent of the lesion (ANOVA main effect of treatment p = 0.26; Figures 6A,B) or total neuron sparing according to area under the neuron by distance curve (ANOVA p = 0.98; Figure 6C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AZM administration significantly reduced the mean rostral-caudal lesion length when given 30 min after injury ( p = 0.03; Figures 5A,B); the 3-h delivery timepoint was not statistically significant ( p = 0.55; Figure 5). Given that pro-inflammatory macrophages are neurotoxic and that AZM limits this activation in vitro we sought to quantify whether post-SCI AZM treatment improved the number of surviving neurons at 28 dpi (Zhang et al, 2015, 2019). However, AZM treatment did not affect neuron sparing throughout the rostral-caudal extent of the lesion (ANOVA main effect of treatment p = 0.26; Figures 6A,B) or total neuron sparing according to area under the neuron by distance curve (ANOVA p = 0.98; Figure 6C).…”
Section: Resultsmentioning
confidence: 99%
“…More recently, we established that delaying treatment for 30 min post-injury substantially decreases markers associated with pro-inflammatory (M1) macrophage activation while significantly increasing anti-inflammatory (M2) macrophage markers (Gensel et al, 2017). Further, we recently found that AZM decreases neurotoxic, pro-inflammatory macrophage activation independent of its antibiotic properties (Zhang et al, 2019). Collectively, these findings highlight AZM as a promising SCI immunomodulatory therapeutic; however, the long-term effects of delayed AZM treatment are unknown.…”
Section: Introductionmentioning
confidence: 96%
“…The European Union stipulates the residue limits of erythromycin, spiramycin, tilmicosin, and tylosin in milk were 40,200,50, and 50 µg/kg, respectively [7]. Currently, a report that six derivatives or metabolites of macrolides had been found in domestic and industrial wastewater for the first time, and their concentration can up to 20.1 µg/L, which may indirectly pollute crops and foods [8]. Telithromycin, kirromycin, meleumycin, N-demethyl-roxithromycin, N-demethyl-clarithromycin, and erythromycin A oxime were included and their structures are shown in Fig.…”
Section: F I G U R Ementioning
confidence: 99%
“…However, the peak width of neo spiramycin I became broader with the addition of ammonium acetate, and there were also two chromatographic peaks existed in oleandomycin. Therefore, in this experiment, a series of pH (3,4,5,6,7,8,9, and 10) gradients were selected to optimize the peak shapes of neo spiramycin I and oleandomycin. The results showed that the peak shape and peak resolution of each target were relatively good at pH ≤ 3 and pH ≥ 9.…”
Section: F I G U R Ementioning
confidence: 99%
“…A91 modulates the inflammatory and autoreactive response observed following SCI. These effects are carried out by inducing a Th2 response, thus promoting an M2 macrophage phenotype and providing a permissive microenvironment for functional recovery 14‐16 …”
Section: Introductionmentioning
confidence: 99%